Clinical Characteristics of Pregnant Women Who Give Birth Using the Lotus Birth Delivery Method at the Permata Bunda Maternity Clinic 2012-2019 period - Kadek Dwi Cakradiningrat; Putu Sudarsana; Made Bayu Permasutha; Ketut Putra Sedana (Sean Institute, 2023)
The lotus birth method of delivery is a method of delivery that does not involve clamping or cutting the umbilical cord, so the umbilical cord is left with the baby and is connected to the placenta, until the umbilical cord is dry and falls off by itself.(Sedana, 2022). This study aims to determine the clinical characteristics of pregnant women who gave birth using the lotus birth method at the Permata Bunda Maternity Clinic for the period 2012 – 2019. The location of this research is located at the Permata Bunda Maternity Clinic, Buleleng Regency, Bali Province. This type of research is descriptive observational research with a cross-sectional research design. The population used in this study were all pregnant women who gave birth using the lotus birth method at the Permata Bunda Maternity Clinic for the period June 2012 - December 2019. The sample for this study was taken using a random sampling technique that met the research inclusion criteria. The variables in this study were the patient's age, weight, gestational age, uterine fundal height, blood pressure, parity, previous delivery method, and pregnancy spacing. The data obtained will be presented using Microsoft Excel software and analyzed using the SPSS (Statistical Package For Social Science) program. The data that has been collected will be processed and presented in table form. Based on the results of research conducted regarding the characteristics of pregnant women who gave birth using the lotus birth delivery method at the Permata Bunda Maternity Clinic for the period 2012-2019, the following conclusions were obtained: from the results of this study it was found that (87.9%) of the subjects of this study were aged 20-35 years , (60.6%) multigravida, (60.6%) had a pregnancy interval of more than 1 year, (100%) gave birth vaginally, had an average body weight (64.83 kg), (100%) patients gave birth at term ( term), (78.8%) uterine fundal height according to gestational age, and (100%) normal blood pressure.